Local planning practice and flood risk management in England: is there a collective implementation deficit? - Richards, Juliet; White, Iain; Carter, Jeremy (Environnement Urbain / Urban Environment, 2008)
AbstractAlthough planning policy enables local planning authorities to influence development with regard to flood risk, in practice there appears to be a number of barriers inhibiting effective flood mitigation, particularly in areas with high development pressures. This research focuses on treatment of flood risk within the English local planning system and discovers that there is a seeming failure to capture strategic, collective flood management opportunities, resulting in an implementation deficit between the aims of planning policy and its practical application. Improvements to local planning policy frameworks are needed therefore, to enable the use of more strategic solutions without compromising local development needs.